2014
DOI: 10.1016/j.neuropharm.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Sensitized nucleus accumbens dopamine terminal responses to methylphenidate and dopamine transporter releasers after intermittent-access self-administration

Abstract: Long-access methylphenidate (MPH) self-administration has been shown to produce enhanced amphetamine potency at the dopamine transporter and concomitant changes in reinforcing efficacy, suggesting that MPH abuse may change the dopamine system in a way that promotes future drug abuse. While long-access self-administration paradigms have translational validity for cocaine, it may not be as relevant a model of MPH abuse, as it has been suggested that people often take MPH intermittently. Although previous work ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…Increased D 2 sensitivity in our limited access mice was observed 24hrs following removal of the HF diet, so it is possible that enhanced D 2 sensitivity may be related to acute withdrawal from HF. AMPH exposure, however, reduced autoreceptor function in the limited access group, in line with the classical development of behavioral sensitization, and other reports showing that repeated psychostimulant exposure is associated with reduced D 2 autoreceptor function (Calipari and Jones, 2014; Mateo et al, 2005). The reduced ability of quinpirole to regulate presynaptic dopamine release suggests that decreased D 2 function after repeated AMPH likely drove the enhanced behavioral sensitization we observed in mice with limited access to HF.…”
Section: Discussionsupporting
confidence: 85%
“…Increased D 2 sensitivity in our limited access mice was observed 24hrs following removal of the HF diet, so it is possible that enhanced D 2 sensitivity may be related to acute withdrawal from HF. AMPH exposure, however, reduced autoreceptor function in the limited access group, in line with the classical development of behavioral sensitization, and other reports showing that repeated psychostimulant exposure is associated with reduced D 2 autoreceptor function (Calipari and Jones, 2014; Mateo et al, 2005). The reduced ability of quinpirole to regulate presynaptic dopamine release suggests that decreased D 2 function after repeated AMPH likely drove the enhanced behavioral sensitization we observed in mice with limited access to HF.…”
Section: Discussionsupporting
confidence: 85%
“…MPH exhibits an inverted "U"-shaped profile that is indicative of a dopamine transporter blocker ( Fig. 4A; Ferris et al, 2012;Calipari et al, 2014b). ANOVA revealed a main effect of MPH on dopamine release (F 3,80 5 11.89, P , 0.05).…”
Section: Resultsmentioning
confidence: 93%
“…Previously published work from our laboratory has shown that, although MPH is a DAT blocker, it is affected by changes at the DAT that alter releaser potency, possibly due to the amphetamine-like structure of the compound (Calipari et al, , 2014bFerris et al, 2012). DAT binding is highly dependent on structural components; accordingly, work has shown that MPH binds to the DAT in a fashion that is similar to amphetamine (Wayment et al, 1999;Dar et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Because the striatal DA system is an important site of action for many drugs of abuse (Calipari and Jones, 2014; Calipari et al, 2014), including ethanol (Yim et al, 1998), we examined changes in presynaptic DA kinetics in a mouse model of dependence (Becker and Hale, 1993). In summary, our data show that CIE produces a pattern of presynaptic DA signaling changes, including decreased DA release, increased DA uptake, and D2 autoreceptor supersensitivity, resulting in functional hypodopaminergia during withdrawal.…”
Section: 4 Conclusionmentioning
confidence: 99%